Strategic equity compensation: A delphi-AHP approach to industry-specific governance design for RSUs - Won Albert Park; Elena Sernova; Cheong-Yeul Park (PLoS ONE, 2026)
This study views RSUs (Restricted Stock Units) as a strategic tool to achieve sustainable growth, shareholder value enhancement, and key talent retention, and proposes RSUs introduction and operation framework for Korean companies. To this end, a three-round Delphi survey was conducted with 31 experts (11 from the legal and accounting group and 20 from the strategy, HR, and IR group), to derive key decision-making items for each stage of ‘strategy setting, execution, evaluation and control’. The panel size fits the appropriate range of existing research, and the content validity and level of agreement were statistically verified using CVR (Content Validity Ratio) and Kendall’s W (Kendall’s coefficient of concordance (W)). Subsequently, based on the industrial classification system GICS (Global Industry Classification Standard), four industries were classified (consumer goods, resources and energy, industry and infrastructure, technology and communications) and a total of 48 leaders, including C-level, executives, and team leaders, were selected across the four industry groups (12 per group) as panelists and the relative importance and priorities of each item were calculated based on the criterion of a CR(Consistency Ratio below 0.1. The AHP (Analytic Hierarchy Process) results of the legal and accounting groups showed that ‘Compliance with relevant standards’ and ‘Preparation for audit and supervision response’ were the top factors, suggesting that the stability of RSUs operations is dependent on regulatory compliance and external supervision response capabilities. In the areas of strategy, HR, and IR, the importance of the strategy execution stage was higher than the strategy setting, evaluation, and control stage in all industries. Consumer goods, technology and communications industries evaluated ‘Core talent incentives’ and ‘Incentive model diversification’ as key priorities, while resource/energy and industrial/infrastructure industries evaluated ‘RSUs retention period’ and ‘Short and long-term performance evaluation model’ as key priorities. This study contributes by addressing the limitations of previous studies that only derived the relationship between variables such as RSUs introduction or vesting period and scale and financial performance and analyzing RSUs introduction and operation from the perspective of the process of ‘strategic setting-execution-evaluation and control’. It also demonstrated empirically that a strategy that reflects the characteristics of each industry is needed rather than a uniform introduction of RSUs, provides policy and practical implications for preparing Korea’s RSU guidelines, and can serve as a strategic benchmark for countries or companies with similar environments. Unfortunately, this study does not include the financial and healthcare industries, so further research is needed. Additionally, although Delphi-AHP presents priorities, it cannot verify the causal relationship of RSUs on financial performance or shareholder value, so the results of this study can be extended to follow-up verification studies applied to actual data.